2015
DOI: 10.15835/nbha.43.1.9794
|View full text |Cite
|
Sign up to set email alerts
|

Tilia sp. - Urban Trees for Future

Abstract: Tilia spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Some authors reported that before shedding, metals are remobilized to nonsenescent plant parts, thus higher accumulation of metals in young leaves compared to mature leaves. This can be a possible reason of higher metal contents in young leaves compared to old leaves, as reported in Tilia Europoea [183] and Aesculus hippocastanum [184]. Moreover, redistribution of metals in plant after foliar uptake is generally an indication of phloem transport [185].…”
Section: Effect Of Plant Morphological Characteristics On Foliar Uptamentioning
confidence: 89%
“…Some authors reported that before shedding, metals are remobilized to nonsenescent plant parts, thus higher accumulation of metals in young leaves compared to mature leaves. This can be a possible reason of higher metal contents in young leaves compared to old leaves, as reported in Tilia Europoea [183] and Aesculus hippocastanum [184]. Moreover, redistribution of metals in plant after foliar uptake is generally an indication of phloem transport [185].…”
Section: Effect Of Plant Morphological Characteristics On Foliar Uptamentioning
confidence: 89%